Do Digital Literacy and Collaboration Skills Matter for Cognitive Competence in Vocational Education? - Amallia Putri Octavia; Mohammad Wildan Habibi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the relationships between digital literacy, collaboration skills, and the cognitive competence of vocational high school students. A quantitative approach with a correlational research design was employed. Data were collected through cognitive competence tests and questionnaires measuring students’ digital literacy and collaboration skills. Multiple linear regression was used to examine the extent to which digital literacy and collaboration skills were individually and jointly associated with students’ cognitive competence. The results revealed that digital literacy was positively and significantly associated with cognitive competence (β = 0.302, p = 0.004), whereas collaboration skills showed a positive but non-significant association with cognitive competence when analyzed separately (β = 0.062, p = 0.551). In the simultaneous analysis, digital literacy and collaboration skills were jointly and significantly associated with cognitive competence (F = 9.224, p < 0.001), with the model explaining 11.9% of the variance in cognitive competence (R² = 0.119). These findings indicate that digital literacy is a significant individual predictor of cognitive competence, whereas collaboration skills do not demonstrate a statistically significant individual contribution. However, when considered simultaneously, digital literacy and collaboration skills are significantly associated with cognitive competence. This study contributes to the literature on vocational education by providing empirical evidence regarding the relationships among digital literacy, collaboration skills, and cognitive competence among vocational students. However, the study is limited to one vocational specialization and two independent variables. Future research should therefore involve more diverse samples and incorporate additional relevant variables to provide a more comprehensive understanding of the factors associated with students’ cognitive competence.